2007
DOI: 10.1016/j.psychres.2006.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Stereologic analysis of the lateral geniculate nucleus of the thalamus in normal and schizophrenic subjects

Abstract: Reduction of volume and neuronal number has been found in several association nuclei of the thalamus in schizophrenic subjects. Recent evidence suggests that schizophrenic patients exhibit abnormalities in early visual processing and that many of the observed perceptual deficits are consistent with dysfunction of the magnocellular pathway, i.e. the visual relay from peripheral retinal cells to the two ventrally located magnocellular layers of the lateral geniculate nucleus (LGN). The present study was undertak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 64 publications
5
49
2
Order By: Relevance
“…5,6 In a histologic study, 12 it varied from 66 to 157 mm 3 ; among individuals, the variation was 2-to 3-fold. In our search of the literature, 2 (B).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…5,6 In a histologic study, 12 it varied from 66 to 157 mm 3 ; among individuals, the variation was 2-to 3-fold. In our search of the literature, 2 (B).…”
Section: Discussionmentioning
confidence: 97%
“…There is increasing interest in assessing the MGN and LGN in healthy subjects and in patients with ophthalmic diseases such as glaucoma. [1][2][3][4][5][6] However, current imaging methods for identifying the MGN and LGN vary, and imaging findings are inconsistent. Technical advances in neuroimaging facilitate the study of subcortical structures in vivo.…”
mentioning
confidence: 99%
“…Those structures include the suprachiasmatic nucleus, the pretectum area, the pulvinar and the superior colliculus, which is strongly involved in the visuomotor coordination (Forrester, 2002). So far, no change in the total cell numbers (Selemon & Begovic, 2007) or the volume (Lesch and Bogerts, 1984) of the LGN has been observed but some alterations in optic radiations, connecting the LGN to various areas of the visual cortex were found in schizophrenia (Butler et al, 2006). Lesions of the optic radiations are known to cause visual field defects.…”
Section: The Relay Structuresmentioning
confidence: 99%
“…The finding of Schechter et al (2005) of reduced VEP response to isoluminant colour stimulation is therefore not what one would expect from a purely magnocellular deficit. Selemon and Begovic (2007) examined cell number and volume in the lateral geniculate nucleus (LGN) in post mortem brains of schizophrenic individuals and found that both of these measures were normal in both the magno-and parvocellular layers. These findings do not support the notion of a link between magnocellular deficits and schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Butler and Javitt concluded their 2005 review with the words: 'Results from behavioral and electrophysiological studies support early visual processing dysfunction in schizophrenia, with preferential deficits being found in the magnocellular pathway, though parvocellular deficits have been found as well' (Butler and Javitt 2005, p 156). Based on this statement and the lack of evidence for magnocellular deficits from contrast sensitivity studies, the problems of linking backward masking and VEP responses unequivocally to the magnocellular system, along with the just mentioned negative observations of Selemon and Begovic (2007), it is unclear if, or to what extent, sensory deficiencies in schizophrenia are specific to the magnocellular system.…”
Section: Introductionmentioning
confidence: 99%